The Effect of Minimum Quantity Lubrication (MQL) and Depth of Cut on Surface Roughness in Turning of AISI 1020 Steel - Rahul, Rahul; Rismanto, Muhammad; Iqbal, Muhammad; Sirajuddin, Awal Syahrani; Asmara, Anjar; Hair, Jumadil (Jurnal Rekayasa Mesin, 2026)
This study aims to investigate the effect of the Minimum Quantity Lubrication (MQL) method using wasted cooking oil and depth of cut on surface roughness in the turning process of AISI 1020 steel. The tests were conducted on a manual lathe machine with a spindle speed of 800 rpm, a cutting length of 100 mm, and depth of cut values of 0.2 mm, 0.4 mm, and 0.6 mm. The independent variables used were MQL with wasted cooking oil and depth of cut, while the dependent variable observed was surface roughness. The test results show that the lowest surface roughness (Ra) value of 1.423 µm was obtained at a depth of cut of 0.2 mm with MQL. Conversely, the highest surface roughness value of 3.515 µm was recorded at a depth of cut of 0.6 mm without MQL. Increasing the depth of cut resulted in an increase in surface roughness. However, the application of the MQL method with wasted cooking oil can reduce surface roughness compared to the turning process without MQL. Therefore, the combination of wasted cooking oil as an MQL lubricant and optimal depth of cut can improve surface quality and support the principles of green manufacturing by utilizing wasted cooking oil, which helps reduce the environmental impact of industrial waste.